Recombinant production of plant lectins in microbial systems for biomedical application – the frutalin case study - Oliveira, Carla; Teixeira, José A.; Domingues, Lucília (Frontiers in Plant Science, 2014)
Frutalin is a homotetrameric partly-glycosylated alpha-D-galactose-binding lectin of biomedical interest from Artocarpus incisa (breadfruit) seeds, belonging to the jacalin-related lectins family. As other plant lectins, frutalin is a heterogeneous mixture of several isoforms possibly with distinct biological activities. The main problem of using such lectins as biomedical tools is that “batch-to-batch” variation in isoforms content may lead to inconstant results. The production of lectins by recombinant means has the advantage of obtaining high amounts of proteins with defined amino-acid sequences and more precise properties. In this mini review, we provide the strategies followed to produce two different forms of frutalin in two different microbial systems: Escherichia coli and Pichia pastoris. The processing and functional properties of the recombinant frutalin obtained from these hosts are compared to those of frutalin extracted from breadfruit. Emphasis is given particularly to recombinant frutalin produced in P. pastoris, which showed a remarkable capacity as biomarker of human prostate cancer and as apoptosis-inducer of cancer cells. Recombinant frutalin production opens perspectives for its development as a new tool in human medicine.